Role of branchiomotor neurons in controlling food intake of zebrafish larvae. (3rd July 2017) - Allen, James R.; Bhattacharyya, Kiran D.; Asante, Emilia; Almadi, Badr; Schafer, Kyle; Davis, Jeremy; Cox, Jane; Voigt, Mark; Viator, John A.; Chandrasekhar, Anand
Abstract: The physical act of eating or feeding involves the coordinated action of several organs like eyes and jaws, and associated neural networks. Moreover, the activity of the neural networks controlling jaw movements (branchiomotor circuits) is regulated by the visual, olfactory, gustatory and hypothalamic systems, which are largely well characterized at the physiological level. By contrast, the behavioral output of the branchiomotor circuits and the functional consequences of disruption of these circuits by abnormal neural development are poorly understood. To begin to address these questions, we sought to evaluate the feeding ability of zebrafish larvae, a direct output of the branchiomotor circuits, and developed a qualitative assay for measuring food intake in zebrafish larvae at 7 days post-fertilization. We validated the assay by examining the effects of ablating the branchiomotor neurons. Metronidazole-mediated ablation of nitroreductase-expressing branchiomotor neurons resulted in a predictable reduction in food intake without significantly affecting swimming ability, indicating that the assay is robust. Laser-mediated ablation of trigeminal motor neurons resulted in a significant decrease in food intake, indicating that the assay is sensitive. Importantly, in larvae of a genetic mutant with severe loss of branchiomotor neurons, food intake was abolished. These studies establish a foundation for dissecting the neural circuits driving a motor behavior essential for survival.